The Relationship between Bullying Types and Social Supports in South Sulawesi, Indonesia - Syahruddin Mahmud; Hasmirati Hasmirati (Lembaga Sembilan Tiga Community, 2021)
This study employed a quantitative research method with 545 samples selected among senior high school students. Bullying occurs in many forms in South Sulawesi schools. Verbal bullying has been identified to be the most dominant bullying type. Social supports could minimize the effects and prevalence of bullying in school. The research also found that bullying type is significantly correlated with the existence of social supports in school. Therefore, social support is crucial for students.